2011
DOI: 10.1085/jgp.201010592
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of RyR permeability reveals a role of calsequestrin in termination of SR Ca2+ release in skeletal muscle

Abstract: The mechanisms that terminate Ca2+ release from the sarcoplasmic reticulum are not fully understood. D4cpv-Casq1 (Sztretye et al. 2011. J. Gen. Physiol. doi:10.1085/jgp.201010591) was used in mouse skeletal muscle cells under voltage clamp to measure free Ca2+ concentration inside the sarcoplasmic reticulum (SR), [Ca2+]SR, simultaneously with that in the cytosol, [Ca2+]c, during the response to long-lasting depolarization of the plasma membrane. The ratio of Ca2+ release flux (derived from [Ca2+]c(t)) over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
82
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(98 citation statements)
references
References 45 publications
15
82
1
Order By: Relevance
“…Sztretye et al (20) showed that long-lasting membrane depolarization in myofibers under voltage clamp causes only partial calcium store depletion; their finding is in agreement with the present evidence that depolymerization may be graded and remains limited during normal muscle function. The same work showed that depletion is partial because RyR channels close before the SR is fully depleted.…”
Section: The Changes In Calsequestrin Mobility Are Explained By Itssupporting
confidence: 92%
See 1 more Smart Citation
“…Sztretye et al (20) showed that long-lasting membrane depolarization in myofibers under voltage clamp causes only partial calcium store depletion; their finding is in agreement with the present evidence that depolymerization may be graded and remains limited during normal muscle function. The same work showed that depletion is partial because RyR channels close before the SR is fully depleted.…”
Section: The Changes In Calsequestrin Mobility Are Explained By Itssupporting
confidence: 92%
“…In all other experiments illustrated in Fig. 1A, the fast calcium buffer BAPTA [1,2-bis(o-aminophenoxy)ethane-N,N,N′,N′-tetraacetic acid] was present in the internal solution to reduce calcium-dependent inactivation of the RyR channels (20). The presence of BAPTA increases the flux of calcium release and results in a sharper hump, which can be revealed using much briefer pulses, in turn, making elaborate kinetic studies feasible.…”
Section: Resultsmentioning
confidence: 99%
“…This termination, which is essential for rapid contractile relaxation, requires fast closing of SR Ca 2ϩ release (RyR) channels. Some evidence indi-cates that Casq is required for adequate channel closure in skeletal muscle (13,14), but the issue remains controversial (15). Much of the interest in the properties of this protein stems from observations of linkage between its mutations and human disease (special cases of "couplonopathies" or diseases of the couplon (19)).…”
Section: Calsequestrin 1 Is the Principal Camentioning
confidence: 99%
“…This is similar to cardiac myocytes where SR and cytosolic calcium concentrations play a role in calcium induced calcium release (CICR) from the SR via ryanodine receptors (RyRs, Sobie et al, 2002;Sobie and Lederer, 2012). Similar to cardiac myocytes, recent studies have also shown that calsequestrin, a Ca 2 þ binding protein in the SR, may also help regulate termination or inactivation of Ca 2 þ release from the SR (Berchtold et al, 2000;Ikemoto et al, 1989;Kawasaki and Kasai, 1994;Sztretye et al, 2011).…”
Section: Discussionmentioning
confidence: 75%